The rhetoric of Hindu India: language and urban nationalism - Basu, Manisha Shodhan (Cambridge University Press, 2017)
Introductory matters : the strange case of secular India -- Time's victims in a second republic : new histories, new temporalities -- To make free and let die : the economics of metropolitan Hindutva -- A power over life and rebirth : V.D. Savarkar and the essentials of Hindutva -- Between death and redemption : Hindu India and its antique others -- The after-life of Indian writing in English : telematic managers, journalistic mantras